1986
DOI: 10.1128/mcb.6.9.3232-3239.1986
|View full text |Cite
|
Sign up to set email alerts
|

Immunologically Distinct p53 Molecules Generated by Alternative Splicing

Abstract: Transfection of a functional cloned p53 gene into an L12 p53 nonproducer cell line efficiently reconstituted p53 expression. The p53 protein synthesized in these clones was indistinguishable from that occurring naturally in tumor cells. When a p53 cDNA clone was used instead, we observed that the L12-derived clones exhibited a distinct immunological profile. In the present experiments we compared the immunological epitopes of p53 proteins encoded by several full-length cDNA clones. Immunoprecipitation of p53 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Until the late 1990s, although several important cases of alternative splicing had been described, such as mammalian immunoglobulins 18 and T-cell receptors, 19 the p53 gene, 20 various growth factors, [21][22][23] the CD44 receptor involved in a variety of lymphocyte functions, 24 myofibrillar proteins 25 (tropomyosin, myosin, titin, etc. ), P-element transposase, 26 the sex differentiation pathway of Drosophila melanogaster 27 and, later, other insects, 28 and many others, alternative splicing was considered to be a relatively rare phenomenon occurring, for instance, in about 5% of human genes.…”
Section: Prevalence Of Alternative Splicingmentioning
confidence: 99%
“…Until the late 1990s, although several important cases of alternative splicing had been described, such as mammalian immunoglobulins 18 and T-cell receptors, 19 the p53 gene, 20 various growth factors, [21][22][23] the CD44 receptor involved in a variety of lymphocyte functions, 24 myofibrillar proteins 25 (tropomyosin, myosin, titin, etc. ), P-element transposase, 26 the sex differentiation pathway of Drosophila melanogaster 27 and, later, other insects, 28 and many others, alternative splicing was considered to be a relatively rare phenomenon occurring, for instance, in about 5% of human genes.…”
Section: Prevalence Of Alternative Splicingmentioning
confidence: 99%
“…The alternative splicing discussion by Wolf and colleagues [144][145][146] produces immunologically different p53 molecules. In this publication, they provided the first experimental proof that variably spliced p53 exists in normal cells of many tissues and is not a transformationspecific event type.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A rat embryo fibroblast 2. The MDM-2 cosmid and the vector for this murine gene CV001 [143][144][145] that can bind to p53-R175H to reactivate p53-R175H. Hotspot mutations cause the encoding of mutant p53 proteins, which gain functions that promote the growth of cancer while losing the classical wild-type p53 capabilities.…”
Section: Chromatographymentioning
confidence: 99%
“…Like its human TP53 homolog, the murine Trp53 gene encodes multiple isoforms differing in their N– or C-termini (Arai et al, 1986; Marcel et al, 2011). Mouse models to evaluate the role of p53 isoforms differing in their N-terminus revealed that Δ40-p53 overexpression leads to accelerated ageing (Maier et al, 2004; Steffens Reinhardt et al, 2020).…”
Section: Introductionmentioning
confidence: 99%